SOME INTEGRAL INEQUALITIES OF THE HADAMARDAND FEJER-HADAMARD TYPE VIA GENERALIZED FRACTIONAL INTEGRAL OPERATOR - Abbas, G.; Farid, G. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2018)
In this paper, we give the Hadamard and the Fejer-Hadamard type integral inequalities for convex and relative convex functions by involving a generalization of the Riemann-Liouville fractional integral. Also, some connections with known results have been obtained.